A pre-processing method of internal thermal mass for building energy simulation software. Issue 3 (4th May 2021) - Li, Weilin; Yang, Liu; Zhu, Jiayin; Li, Ruixin
Abstract : It is challenging to accurately establish the dynamic heat transfer model of the internal thermal mass owing to the irregular shape. In building energy simulation software, the internal thermal mass is described as slabs. However, the parameter setting of the equivalent slabs depends primarily on the user experience, which may lead to uncontrollable errors. Therefore, this paper proposes a method, termed the effective area method (EAM), which specifies the transformation of an irregular internal thermal mass to the slab and can be used as a pre-processing method for building simulation software. This paper describes the methodology and pre-processing logic of the EAM, and the implementation of the approach in EnergyPlus considering an office environment. The root-mean-square errors between the simulation and measured temperatures are less than 0.3°C, which indicates that the EAM can effectively eliminate the errors caused by the unreasonable settings of the internal thermal mass.